Identifikasi Potensi Sub Sektor Tanaman Bahan Makanan Di Kabupaten Kubu Raya - B01110017, Muhamad Riansyah (Jurnal Curvanomic, 2017)
Tanaman Bahan Makanan, Pertanian.ABSTRACTThe title of this research is "Identification of Potential Food Crops Sub Sector In the district of Kubu Raya". The purpose of this study is to investigate the food crops that become basis in each District in Kubu Raya, as well as how the proportional growth and competitiveness in the commodity base generated, thus forming a priority the development of the commodity as consideration for Kubu Raya.In this study the author uses descriptive method obtained from the Central Bureau of Statistics Agency of West Kalimantan Province and the Central Bureau of Statistics Kubu Raya. And this study authors used a combination between LQ analysis, and Shift Share to answer the problem of this thesis.from the research result is that each district had its own commodity base generated by each district, commodities of food crops Cassava and Rice is one of the commodities that form the basis in most districts, while the type of plant fruits and vegetables and medicinal plants each commodity Districts have different bases. Their prioritization makes every district appeared to have potential to be developed to be maximal.Keywords: Sub Sectors of Food Crops Plant, Agriculture